Executive Functions Contribute Uniquely to Reading Competence in Minority Youth. (July 2017) - Jacobson, Lisa A.; Koriakin, Taylor; Lipkin, Paul; Boada, Richard; Frijters, Jan C.; Lovett, Maureen W.; Hill, Dina; Willcutt, Erik; Gottwald, Stephanie; Wolf, Maryanne; Bosson-Heenan, Joan; Gruen, Jeffrey R.; et al.
Competent reading requires various skills beyond those for basic word reading (i.e., core language skills, rapid naming, phonological processing). Contributing "higher-level" or domain-general processes include information processing speed and executive functions (working memory, strategic problem solving, attentional switching). Research in this area has relied on largely Caucasian samples, with limited representation of children from racial or ethnic minority groups. This study examined contributions of executive skills to reading competence in 761 children of minority backgrounds. Hierarchical linear regressions examined unique contributions of executive functions (EF) to word reading, fluency, and comprehension. EF contributed uniquely to reading performance, over and above reading-related language skills; working memory contributed uniquely to all components of reading; while attentional switching, but not problem solving, contributed to isolated and contextual word reading and reading fluency. Problem solving uniquely predicted comprehension, suggesting that this skill may be especially important for reading comprehension in minority youth. Attentional switching may play a unique role in development of reading fluency in minority youth, perhaps as a result of the increased demand for switching between spoken versus written dialects. Findings have implications for educational and clinical practice with regard to reading instruction, remedial reading intervention, and assessment of individuals with reading difficulty.